The innocent - Coben, Harlan, 1962- (Dutton, 2017)
One night, Matt Hunter innocently tried to break up a fight--and ended up a killer. Now, nine years later, he's an ex-con who takes nothing for granted. His wife, Olivia, is pregnant, and the two of them are closing on their dream house. But all it will take is one shocking, inexplicable call from Olivia's cell phone to shatter Matt's life a second time.